Polymeric Chitosan/Poly (Vinyl Alcohol) Hybrid Doped with Zinc Oxide Nanoparticles Synthesized and Characterized Using the Electrospun Method (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:Because of their portability and flexibility in altering surface properties, nanofibers have attracted more attention in recent years, particularly in biological applications. The development of affordable antibacterial base agents for wound healing capabilities and other medical technologies is still in high demand. Porosity, ease of forming into different sizes, and high surface area are just a few of the benefits of nanofibers.Materials and Methods:A 90% deacetylated (average 200,000 MW) poly(vinyl alcohol) chitosan with a life of 72000 MW was bought.Results:Through the samples of the electronic scanner, electrospinning rates, flow of 0.6 ml / sec, voltage of 10 kV, distance between the collector and the needle of 8 cm, and the ratio of PVA / CS / ZnO to the polymer with the addition of nanoparticles ratio 0.4% 65 / 35.Conclusion:In this study, the nanofiber compound PVA / CS / ZnO proved to have medical and biological compatibility. There is no toxicity in this compound. It has therapeutic properties against microbes and is good in healing wounds, as in previous studies